Skip-beat! 20 - Nakamura, Yoshiki (Shojo beat manga., 2010)
Kyoko gets Maria to admit what has her so soured on the holidays. It turns out December 24th is Maria's birthday and the anniversary of her mother's death. Can Kyoko work a Christmas miracle and give this little girl a happy birthday?